Ageing mechanism of gold and silver nanorods in aqueous solution - Segets, Doris; Damm, Cornelia; Vieweg, Benito; Yang, Guang; Spiecker, Erdmann; Peukert, Wolfgang (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites - 2010 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2010, 2010)
The current work addresses the understanding of the shape transformation of silver and gold nanorods towards more spherical nanostructures in aqueous suspension at ambient temperature. The shape transformation process was characterised using UV/Vis absorption spectroscopy, scanning electron microscopy (SEM), anodic stripping voltammetry and high resolution transmission electron microscopy (HRTEM). The increase in the particle number density during ageing indicates that the rods break spontaneously in smaller particles by surface defect induced ripening.
Keywords: Ageing; Gold nanorods; Optical characterization; Shape stability; Silver nanorods

Low-Voltage p- and n-Type Organic Self-Assembled Monolayer Field Effect Transistors - Novak, Michael; Ebel, Alexander; Meyer-Friedrichsen, Timo; Jedaa, Abdesselam; Vieweg, Benito; Yang, Guang; Voitchovsky, Kislon; Stellacci, Francesco; Spiecker, Erdmann; Hirsch, Andreas; Halik, Marcus (Nano Letters, 2011)
We report on p- and n-type organic self-assembled monolayer field effect transistors. On the base of quaterthiophene and fullerene units, multifunctional molecules were synthesized, which have the ability to self-assemble and provide multifunctional monolayers. The self-assembly approach, based on phosphonic acids, is very robust and allows the fabrication of functional devices even on larger areas. The p- and n-type transistor devices with only one molecular active layer were demonstrated for transistor channel lengths up to 10 μm. The monolayer composition is proven by electrical experiments and by high-resolution transmission electron microscopy, electron energy loss spectroscopy, XPS, and AFM experiments. Because of the molecular design and the contribution of isolating alkyl chains to the hybrid dielectric, our devices operate at low supply voltages (-4 V to +4 V), which is a key requirement for practical use and simplifies the integration in standard applications. The monolayer devices operate in ambient air and show hole and electron mobilities of 10 cm/(V s) and 10 cm/(V s) respectively. In particular the n-type operation of self- assembled monolayer transistors has not been reported before. Hereby, structure-property relations of the SAMs have been studied. Furthermore an approach to protect the sensitive C from immediate degradation within the molecular design is provided. © 2011 American Chemical Society.

Morphological impact of zinc oxide layers on the device performance in thin-film transistors - Faber, Hendrik; Klaumünzer, Martin; Voigt, Michael; Galli, Diana; Vieweg, Benito; Peukert, Wolfgang; Spiecker, Erdmann; Halik, Marcus (Nanoscale, 2011)
Zinc oxide thin-films are prepared either by spin coating of an ethanolic dispersion of nanoparticles (NP, diameter 5 nm) or by spray pyrolysis of a zinc acetate dihydrate precursor. High-resolution electron microscopy studies reveal a monolayer of particles for the low temperature spin coating approach and larger crystalline domains of more than 30 nm for the spray pyrolysis technique. Thin-film transistor devices (TFTs) based on spray pyrolysis films exhibit higher electron mobilities of up to 24 cm² V−1 s−1 compared to 0.6 cm² V−1 s−1 for NP based TFTs. These observations were dedicated to a reduced number of grain boundaries within the transistor channel.

P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.

Shape Transformation Mechanism of Silver Nanorods in Aqueous Solution - Damm, Cornelia; Segets, Doris; Yang, Guang; Vieweg, Benito; Spiecker, Erdmann; Peukert, Wolfgang (Small, 2011)
The spontaneous shape transformation of silver nanorods with an initial length of several hundred nanometers towards spherical particle shapes in aqueous solution is investigated by means of scanning electron microscopy, UV–vis absorption spectroscopy, anodic stripping voltammetry, and high-resolution transmission electron microscopy (HRTEM). The consolidation of the results reveals an increase in the particle number density with time. Moreover, HRTEM image analysis along the cross section of the rods evidences the presence of fivefold twinning defects which extend along the whole rod length. According to the analytical model of Monk et al. this kind of rod structure is only thermodynamically stable if the rod length is below a critical value at a given diameter. The rods investigated in the present work do not fulfill the stability criterion as they exceed the critical length. Thus, the rods decay into smaller “nanobuns” and defective as well as defect-free spheres. A mechanism based on findings from the literature, HRTEM image analysis of former rods, transition states, and the final particle structures is proposed. The defects along the surface are seen as starting points for the dissolution of material, which is reintegrated into the solid phase by homogeneous as well as heterogeneous nucleation and growth.

TEM preparation method for site- and orientation-specific sectioning of individual anisotropic nanoparticles based on shadow-FIB geometry - Vieweg, Benito; Butz, Benjamin; Peukert, Wolfgang; Klupp Taylor, Robin; Spiecker, Erdmann (Ultramicroscopy, 2012)
For the comprehensive characterization of nanoparticles cross-sectional investigation on the atomic scale by analytical and high-resolution transmission electron microscopy (TEM) is indispensable. Cross-sectioning is especially important for anisotropic nanoparticles to gain information on structure and chemistry along all important projections. We present a focused ion beam (FIB) method for site- and orientation-specific cross-sectioning of arbitrary nanoparticles that are dispersed on a substrate. By adopting a shadow geometry originally developed for thin sensitive films' protection of the specimen by a platinum layer is avoided. This enables simultaneous observation (from the front side) by the electron beam and ion-beam sectioning (from the back side of the supporting substrate) of individually selected particles with excellent accuracy on the nanometer scale. The feasibility and general applicability of the method is demonstrated by site-specific sectioning and cross-section HRTEM investigation of two types of anisotropic nanostructures: silver nanorods with five-fold twin structure and Janus-type silver patchy particles. © 2011 Elsevier B.V.
Keywords: FIB; High-resolution transmission electron microscopy; Nanoparticles; Nanorods; Patchy particles; TEM preparation